Impact of intercurrent respiratory infections on lung health in infants born <29 weeks with bronchopulmonary dysplasia. - Taylor, J B; Nyp, M F; Norberg, M; Dai, H; Escobar, H; Ellerbeck, E; Truog, W E (Journal of Perinatology, 2014)
Objective:Assess the impact of intercurrent respiratory infections in infants <29 weeks gestational age (GA).Study design:A retrospective cohort study of 111 infants born <29 weeks GA, controlling for bronchopulmonary dysplasia (BPD) severity and assessing pulmonary health over the first year of life through oxygen, diuretic and inhaled steroid use.Result:Regression analysis showed viral infections increased oxygen use (odds ratio (OR) of 15.5 (confidence interval (CI)=3.4, 71.3)). The trend test showed increasing numbers of viral infections were associated with increased oxygen (OR (95% CI)=6.4 (2.3 to 17.4), P=0.0003), diuretic (OR (95% CI)=2.4 (1.1to 5.2), P=0.02) and inhaled steroid use (OR (95% CI)=2.2 (1.003 to 5.2), P=0.049), whereas bacterial infections were not.Conclusion:Viral infections caused more long-term pulmonary morbidity/mortality than bacterial infections on premature lung health, even when controlling for BPD.